(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Implementation of clinical supervision by supervisors can make an important contribution in improving teacher performance in managing learning that refers to the functions, principles, goals and procedures for implementing optimal supervision. Supervisors need to have professional competence which is the ability to carry out supervision effectively, efficiently and include all activities related to improving teaching and learning as a service to teachers.Overall improvements need to be made to various aspects that lead to less than optimal implementation of clinical supervision such as the reluctance to be supervised and not fully open to the supervisor for the deficiencies and obstacles encountered in learning during initial meetings or pre-observations, influenced by fear, lack of confidence, giving rise to the impression and perception of the teacher, that the supervisor is only a mere assessment activity by looking for weaknesses or weaknesses that the teacher has in learning.